IMPROVEMENT OF HEALTH CARE FINANCING IN THE REGION - T. V. Shchyukina; S. N. Plyuta (Вестник университета)
During implementation of the reforms of the health care financing system in the Russian Federation, new proportions of sources of financial support for this key area were determined, on which the level of health of the population depends, affecting the socio-economic indicators of the development of the state. The fundamental factors, on which depend the volume and sources of financing of health care in the region, have been analyzed in the article. The role of the regional budget as a source of health care financing in more detail on the example of the budget of the Irkutsk region has been considered. Trends and prospects for the development of the health care financing system in the region have been identified.